(untitled) (TEL Tempo, Espaço e Linguagem, 2019)
Abstract: This article explores the theory of performativity of gender proposed by Judith Butler. It aspires to show how, within debates about the construction of gender, performativity is an epistemological alternative that allows us to avoid both essentialist and radical constructivist positions. Keywords: Gender. Performativity of gender. Judith Butler.